Understanding and Tuning Bioinorganic Interfaces for the Design of Bionanocomposites. Issue 27 (14th July 2015) - Voisin, Hugo; Aimé, Carole; Coradin, Thibaud
Abstract: Interactions between biological molecules and inorganic species are of tremendous importance in nature. Attempts to create bionanocomposites associating nanoscale inorganic objects with biomolecules face major challenges with regard to controlling their mutual reactivity and preserving their intrinsic properties. This review describes the interactions arising between polyoxometallates or silica particles and biomolecules – including proteins, polysaccharides, lipids and nucleic acids – that depend on physicochemical conditions. It shows that chemical modification of the inorganic and/or bio‐organic partner allows fine‐tuning of their interface. The specific properties of these bionanocomposites are illustrated, with emphasis on their potential in biotechnology and biomedicine. This field contributes to a better understanding of the "biochemistry of solids" and offers an almost unlimited playground for the elaboration of new materials that combine molecular biodiversity with chemistry in its many facets. Abstract : Understanding and controlling interfacial interactions between biological molecules – from lipids to proteins – and inorganic nano‐objects, polyoxometallates and colloids allows the synthesis of bionanocomposites with applications in biotechnology and biomedicine.